A Premiere example of the illusion of harm reduction cigarettes in the 1990s. Issue 3 (4th September 2003) - Pollay, R W; Dewhirst, T
Abstract : Objective: To use the product launch of Player's Premiere as a case study for understanding the new cigarette product development process during the 1990s. We determine the (in)validity of industry claims that: (1) development of the physical product preceded the promotional promise of "less irritation"; (2) "less irritation" was actually realised; (3) advertising informed consumers; and (4) advertising regulations caused the product's failure in the marketplace. Setting: Court proceedings assessing the constitutionality of Canada's Tobacco Act, which substantially restricts cigarette advertising. The 2002 Quebec Superior Court trial yielded a new collection of internal documents from Imperial Tobacco Ltd (ITL), including several about the development and marketing of Player's Premiere. Method: Trial testimony and corporate documents were reviewed to determine the validity of the industry representations about the new cigarette product development process, focusing on the case history of Player's Premiere. Results: In direct contradiction to industry testimony, the documentary evidence demonstrates that (1) communications for Player's Premiere, which claimed less irritation, were developed long before finding a product that could deliver on the promise; (2) ITL did not sell a "less irritating" product that matched its promotional promise; (3) the advertising and other communications for Player's Premiere were extensive, relying on the hi-tech appearances ("tangible credibility") of a "unique" filter, yet were uninformative and vague; and (4) Player's Premiere failed in the marketplace, despite extensive advertising and retail support, because it was an inferior product that did not live up to its promotional promise, not because of regulation of commercial speech. Conclusions: New product development entails extensive consumer research to craft all communications tools in fine detail. In the case of Player's Premiere, this crafting created a false and misleading impression of technological advances producing a "less irritating" cigarette. This product was solely a massive marketing ploy with neither consumer benefits, nor public health benefits. The industry attempted to deceive both consumers and the court.